The cardioprotective effect of thymoquinone on ischemia‐reperfusion injury in isolated rat heart via regulation of apoptosis and autophagy. Issue 9 (22nd June 2018) - Xiao, Junhui; Ke, Zun‐Ping; Shi, Yan; Zeng, Qiutang; Cao, Zhe
Abstract: Thymoquinone (TQ), as the active constituents of black cumin (Nigella sativa) seed oil, has been reported to have potential protective effects on the cardiovascular system. This study aimed to investigate the effects and the underlying mechanisms of TQ on myocardial ischemia‐reperfusion (I/R) injury in Langendorff‐perfused rat hearts. Wister rat hearts were subjected to I/R and the experimental group were pretreated with TQ prior to I/R. Hemodynamic parameters, myocardial infarct size, cardiac marker enzymes, superoxide dismutase (SOD), malondialdehyde (MDA) content, and cardiomyocyte apoptosis were assayed. Compared with the untreated group, TQ preconditioning significantly improved cardiac function, reduced infarct size, decreased cardiac lactate dehydrogenase (LDH) and creatine kinase‐MB (CK‐MB) levels, suppressed enedoxidative stress, and apoptosis. In addition, TQ treatment promoted autophagy, which was partially reversed by chloroquine (CQ), a kind of autophagy blocker. Our study suggests that TQ can protect heart against I/R injury, which is associated with anti‐oxidative and anti‐apoptotic effects through activation of autophagy. Abstract : We demonstrate that TQ can effectively improve the cardiac function, reduce the myocardial infarct size, decrease the myocardial enzyme activities, and inhibit oxidative stress. The main effects of TQ may be related to its anti‐oxidative and anti‐apoptotic actions involving the modulation of autophagy. Next, futher research should be focused on confirming cardioprotective effect of TQ on I/R in vivo and exploring a novel therapeutic strategy for people suffering from I/R injury.